Integrating the combined sagittal index reduces the risk of dislocation following total hip replacement - Grammatopoulos, George; Falsetto, Amedeo; Sanders, Ethan; Weishorn, Johannes; Gill, Harinderjit S.; Beaulé, Paul E.; Innmann, Moritz Maximilian; Merle, Christian (The journal of bone & joint surgery. A, American volume, 2022)
Background: - The aims of this matched cohort study were to (1) assess differences in spinopelvic characteristics between patients who sustained a dislocation after total hip arthroplasty (THA) and a control group without a dislocation, (2) identify spinopelvic characteristics associated with the risk of dislocation, and (3) propose an algorithm including individual spinopelvic characteristics to define an optimized cup orientation target to minimize dislocation risk. - Methods: - Fifty patients with a history of THA dislocation (29 posterior and 21 anterior dislocations) were matched for age, sex, body mass index (BMI), index diagnosis, surgical approach, and femoral head size with 200 controls. All patients underwent detailed quasi-static radiographic evaluations of the coronal (offset, center of rotation, and cup inclination/anteversion) and sagittal (pelvic tilt [PT], sacral slope [SS], pelvic incidence [PI], lumbar lordosis [LL], pelvic-femoral angle [PFA], and cup anteinclination [AI]) reconstructions. The spinopelvic balance (PI − LL), combined sagittal index (CSI = PFA + cup AI), and Hip-User Index were determined. Parameters were compared between the control and dislocation groups (2-group analysis) and between the controls and 2 dislocation groups identified according to the direction of the dislocation (3-group analysis). Important thresholds were determined from receiver operating characteristic (ROC) curve analyses and the mean values of the control group; thresholds were expanded incrementally in conjunction with running-hypothesis tests. - Results: - There were no coronal differences, other than cup anteversion, between groups. However, most sagittal parameters (LL, PT, CSI, PI − LL, and Hip-User Index) differed significantly. The 3 strongest predictors of instability were PI - LL >10° (sensitivity of 70% and specificity of 65% for instability regardless of direction), CSIstanding of <216° (posterior instability), and CSIstanding of >244° (anterior instability). A CSI that was not between 205° and 245° on the standing radiograph (CSIstanding) was associated with a significantly increased dislocation risk (odds ratio [OR]: 4.2; 95% confidence interval [CI]: 2.2 to 8.2; p < 0.001). In patients with an unbalanced and/or rigid lumbar spine, a CSIstanding that was not 215° to 235° was associated with a significantly increased dislocation risk (OR: 5.1; 95% CI: 1.8 to 14.9; p = 0.001). - Conclusions: - Spinopelvic imbalance (PI − LL >10°) determined from a preoperative standing lateral spinopelvic radiograph can be a useful screening tool, alerting surgeons that a patient is at increased dislocation risk. Measurement of the PFA preoperatively provides valuable information to determine the optimum cup orientation to aim for a CSIstanding of 205° to 245°, which is associated with a reduced dislocation risk. For patients at increased dislocation risk due to spinopelvic imbalance (PI − LL >10°), the range for the optimum CSI is narrower. - Level of Evidence: - Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.